Shopping for Health: Milk - Wendy J. Dahl; Lauren Foster (EDIS)
Consuming milk and milk products can provide many long-term health benefits, but you should know the facts before you shop. Not all types of milk provide the same nutrients. Learn more in this 4-page fact sheet written by Wendy J. Dahl and Lauren Foster, and published by the UF Department of Food Science and Human Nutrition, June 2011.